ASUHAN KEPERAWATAN PADA KLIEN ASMA DENGAN MASALAH BERSIHAN JALAN NAFAS TIDAK EFEKTIF DI KELURAHAN KEBAGUSAN KOTA JAKARTA SELATAN - Bunga Qosimah Rasel (2023)
Background : Asthma is a chronic inflammatory disease characterized by hypersensitivity, swelling of the mucous membranes and mucus production. This inflammation then develops into recurring episodes of asthma symptoms which include chest tightness, coughing, shortness of breath, and wheezing. Patients with asthma may experience disturbances that can last minutes, hours, or days. The purpose of this study is to be able to perform nursing care on asthmatic clients with ineffective airway clearance. Method: The research design used is a descriptive method in the form of a case study.Research results: Obtained the results of research on clients with a diagnosis of asthma, one priority diagnosis has been obtained, namely in the form of ineffective airway clearance related to retained secretions. After 3 days of nursing care, it was found that the client was able to carry out normal activities. Conclusion: It is expected that from the client case Mr. A with asthmatics is a partially insurmountable problem. The advice from this researcher is to maintain a healthy and good lifestyle that aims to prevent the disease from recurring.